What are the challenges for implementing an “organic label” to camel milk? - Konuspayeva, Gaukhar; Faye, Bernard; Nurseitova, Moldir; Akhmetsadykova, Shynar (Frontiers in Nutrition, 2023)
Increasing demand for camel's milk worldwide occurred in the context of the development of the organic sector in agriculture. The implementation of an organic label for camel milk has never been established. However, the creation of such a label faces to important challenges that are investigated in the present paper. Indeed, although camel milk conveys the image of a "natural product" issued from remote places, the risk of being produced in contaminated areas (mining activities, oil extraction) cannot be neglected for grazing animals. Moreover, the management of veterinary drugs for prevention or curative treatment can lead to the presence of residues in milk, especially in camel species with different pharmacokinetics, although similar instructions than for cow milk are used. Moreover, the lack of international standards regarding both composition and hygienic rules, the risks of adulteration, and the necessity to use specific indicators or analytical procedures adapted to the behaviour of camel milk, have to be taken in account in the establishment of the specifications for the camel milk producers through the world.